2022
DOI: 10.1167/jov.22.8.10
|View full text |Cite
|
Sign up to set email alerts
|

Foveal crowding appears to be robust to normal aging and glaucoma unlike parafoveal and peripheral crowding

Abstract: Visual crowding is the inability to recognize a target object in clutter. Previous studies have shown an increase in crowding in both parafoveal and peripheral vision in normal aging and glaucoma. Here, we ask whether there is any increase in foveal crowding in both normal aging and glaucomatous vision. Twenty-four patients with glaucoma and 24 age-matched normally sighted controls (mean age = 65 ± 7 vs. 60 ± 8 years old) participated in this study. For each subject, we measured the extent of foveal crowding u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
2
1
0
Order By: Relevance
“…Contrary to our expectations, we found no worsening of crowding as age increased. These findings are consistent with previous studies showing the absence of increased vulnerability in older adults in identifying a stimulus due to spatially contiguous flankers [ 56 , 57 , 58 ]. However, other studies have reported a significant age-related susceptibility to crowding [ 10 , 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Contrary to our expectations, we found no worsening of crowding as age increased. These findings are consistent with previous studies showing the absence of increased vulnerability in older adults in identifying a stimulus due to spatially contiguous flankers [ 56 , 57 , 58 ]. However, other studies have reported a significant age-related susceptibility to crowding [ 10 , 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear if crowding worsens with age and whether this could contribute to poorer reading performance in older adults as well; some authors argue that the impact of visual crowding increases with age, hence a greater susceptibility to crowding is linked to a worse reading speed [ 10 , 55 ]; on the opposite side, other authors claim that crowding is unaffected by aging, while surround suppression is instead [ 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Males show increased activation in the left hemisphere’s inferior parietal lobule, while females show significant activation in the right hemisphere’s inferior frontal gyrus, insula, caudate, and temporal areas ( de Fockert et al, 2001 ; Boi et al, 2011 ), which may be related to the modulation by estrogen and testosterone ( Oberauer, 2019 ). Additionally, FA was not observed to be affected by gender, age and years of education in this study, which is in line with the results of the most recent application of the scale, i.e., crowding did not worsen with age ( Pegoraro et al, 2024 ), and these findings are consistent with previous studies ( Malavita et al, 2017 ; Shamsi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%